PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA PADA MATA PELAJARAN IPA KELAS VII G SMPN 23 PEKANBARU TAHUN PELAJARAN 2015/2016 - Endah Kurnia Sari; Evi '; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study was conducted in classes VII G SMP 23 Pekanbaru 2015/2016 school year to determine the increase science process skills of students by implementing guided inquiry learning model. This research is a classroom action research conducted in two cycles of planning, execution and observation and reflection. The data collected in this study is the science process skills that emphasizes on three areas, namely knowledge, attitudes and skills. Data were collected using tests and observation sheet. The results showed science process skills in every sphere has increased. Science process skills that emphasize cognitive seen from the results of daily tests on the first cycle that 3.05 (B) is increased in the second cycle is 3.15 (B). Students who complete the first cycle of 25 students (64.10%) and increased in the second cycle is 31 (79.49%). On average students' science process skills in the realm of attitudes in the first cycle, namely 2.90 (B) and increased in the second cycle 3.37 (B). Average science process skills of students who emphasize the domain of skills in the first cycle, namely 2.86 (B) and increased in the second cycle is 3.49 (B+). It can be concluded that the application of guided inquiry learning model can improve science process skills class VII G SMP 23 Pekanbaru in the academic year 2015/2016.Keywords: model of guided inquiry, science process skills